2014
DOI: 10.15376/biores.9.4.6805-6816
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Speed and Press Factor on Oriented Strand Board Performance in Continuous Press

Abstract: a Three-layer cross-oriented strand boards, OSB type 3 of 10 mm thick, were industrially manufactured from a mixture of wood species including 50% softwoods, 25% beech, and 25% low hardwoods, using a continuous press line. The effects of line speed and press factor on physical and mechanical properties of OSB/3 (exterior grade) were evaluated, keeping nearly constant the face-core adhesive ratio. The manufactured boards were classified into five groups depending on the pressing parameters. The experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Penetration of resin reduces the diameters of the capillaries or the total void age, which results in a reduced water uptake. Water uptakes in these OSBs were almost equivalent to those reported for OSBs from softwood and hardwood (Zhang et al 2007;Febrianto et al 2009;Gündüz et al 2011;Ciobanu et al 2014). The values of TS obtained in this experiment did not exceed the OSB minimum property requirement according to the CSA O437.0 (grade O-1) standard.…”
Section: Physical Properties Of Osbsupporting
confidence: 80%
“…Penetration of resin reduces the diameters of the capillaries or the total void age, which results in a reduced water uptake. Water uptakes in these OSBs were almost equivalent to those reported for OSBs from softwood and hardwood (Zhang et al 2007;Febrianto et al 2009;Gündüz et al 2011;Ciobanu et al 2014). The values of TS obtained in this experiment did not exceed the OSB minimum property requirement according to the CSA O437.0 (grade O-1) standard.…”
Section: Physical Properties Of Osbsupporting
confidence: 80%
“…3B). For OSB/3 bonded with pMDI, these results were in agreement with those from Hrázský and Král (2009) Also the present results are consistent with those of Ciobanu et al (2014), who found that the MOR ranged from 22.8 N/mm 2 to 26.8 N/mm 2 and from 12.1 N/mm 2 to 15.4 N/mm 2 parallel and perpendicular to the length axes, respectively, for the OSB/3 board made from a mixture of strands. For the same boards, the MOE ranged from 3934 N/mm 2 to 4769 N/mm 2 and from 1667 N/mm 2 to 2186 N/mm 2 parallel and perpendicular to the length axes, respectively.…”
Section: Physical and Mechanical Properties Of The Osbssupporting
confidence: 93%
“…2B). The lower values of the MOR and MOE were found in the perpendicular direction, which is the minor axis (Ciobanu et al 2014). The average MOE values of OSB/3 ranged from 4515.4 N/mm 2 to 4795.6 N/mm 2 (=, Fig.…”
Section: Physical and Mechanical Properties Of The Osbsmentioning
confidence: 89%
See 2 more Smart Citations